FROM DATA TO DECISION: HOW AI AND FINTECH DRIVE DIGITAL TRANSFORMATION IN RURAL ENTREPRENEURSHIP - Ratri Anggraheni, Dhiptya; Mawaddah, Udkhiati (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study presents a systematic literature review (SLR) examining how Artificial Intelligence (AI) and Financial Technology (FinTech) drive digital transformation in rural entrepreneurship. Based on 20 peer-reviewed studies published between 2020 and 2025, the analysis integrates insights from developed and developing economies using the Resource-Based View (RBV), Diffusion of Innovation (DOI) Theory, Institutional Theory, and Sustainable Livelihoods Framework (SLF). Findings reveal that digital infrastructure serves as the foundation for rural participation in the digital economy, while FinTech promotes financial inclusion through mobile banking, blockchain, and data-driven credit systems. AI enhances decision-making via predictive analytics and automation, improving efficiency across production, logistics, and marketing. Governance quality and human capital development shape institutional readiness and ensure sustainability alignment. This review advances theoretical understanding and offers policy guidance for building inclusive digital ecosystems through adaptive governance, capacity-building, and ethical technology integration, fostering resilient and equitable rural transformation.